2005
DOI: 10.1038/sj.bjc.6602700
|View full text |Cite
|
Sign up to set email alerts
|

The retinoid anticancer signal: mechanisms of target gene regulation

Abstract: Retinoids induce growth arrest, differentiation, and cell death in many cancer cell types. One factor determining the sensitivity or resistance to the retinoid anticancer signal is the transcriptional response of retinoid-regulated target genes in cancer cells. We used cDNA microarray to identify 31 retinoid-regulated target genes shared by two retinoid-sensitive neuroblastoma cell lines, and then sought to determine the relevance of the target gene responses to the retinoid anticancer signal. The pattern of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
(27 reference statements)
5
46
0
Order By: Relevance
“…Previous studies focused on the role of ATP7A in Menke's disease, have shown that ATP7A expression and copper plays an important role in neural differentiation and neuritogenesis (El Meskini et al, 2005Birkaya and Aletta, 2005). We found an increase in cell viability when ATP7A expression was knocked down in neuroblastoma cells (Liu et al, 2005). The significant correlation between ATP7A and RARb expression suggests that ATP7A may contribute to the RARb anti-cancer therapeutic effect.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Previous studies focused on the role of ATP7A in Menke's disease, have shown that ATP7A expression and copper plays an important role in neural differentiation and neuritogenesis (El Meskini et al, 2005Birkaya and Aletta, 2005). We found an increase in cell viability when ATP7A expression was knocked down in neuroblastoma cells (Liu et al, 2005). The significant correlation between ATP7A and RARb expression suggests that ATP7A may contribute to the RARb anti-cancer therapeutic effect.…”
Section: Discussionsupporting
confidence: 55%
“…In a previous study using the cDNA microarray, we found that the copper transporter ATP7A was strongly upregulated in neuroblastoma cells in response to retinoid (Liu et al, 2005). In this study, we found that ATP7A protein expression is upregulated in neuroblastoma cells after retinoid treatment.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…CYP26A1 has been shown to be upregulated in human familial adenomatous polyposis adenomas, sporadic colon cancers and primary ovarian cancer (Downie et al, 2005;Shelton et al, 2006). Furthermore, the pattern of retinoid gene expression, including CYP26A1, has been shown to correlate with retinoid sensitivity in a panel of breast and lung cancer cell lines (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%